2005
DOI: 10.1017/s0265021505001444
|View full text |Cite
|
Sign up to set email alerts
|

Sedation with target-controlled propofol infusion during shoulder surgery under interscalene brachial plexus block in the sitting position

Abstract: Target-controlled propofol infusion (0.8-0.9 microg mL(-1)) following hydroxyzine premedication is a safe and effective technique for sedation when combined with interscalene brachial plexus block during shoulder surgery in the sitting position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…No hypotensive episodes needed treatment in either group, probably because our study population was 18–65 years old and otherwise healthy except for being ASA I or II. Despite the many surgical advantages of this position, sedation and continous observation of the airway and hemodynamics which are of anaesthetic relevance may be difficult in awake patients [ 28 ]. It is known that inadequate sedation in these patients might result in complaints of noise or discomfort from prolonged immobility and can increase the risk of side effects unless there is further improvement in the analgesia quality [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…No hypotensive episodes needed treatment in either group, probably because our study population was 18–65 years old and otherwise healthy except for being ASA I or II. Despite the many surgical advantages of this position, sedation and continous observation of the airway and hemodynamics which are of anaesthetic relevance may be difficult in awake patients [ 28 ]. It is known that inadequate sedation in these patients might result in complaints of noise or discomfort from prolonged immobility and can increase the risk of side effects unless there is further improvement in the analgesia quality [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…[78] Vincent and colleagues used TCI propofol for sedation in patients undergoing shoulder arthroscopic surgery under regional anaesthesia at target plasma concentrations of 0.8-0.9 μg/ml. [4] When TCI propofol is used alone, a plasma concentration of 4-6 μg/ml is necessary to maintain the necessary depth of anaesthesia in ASA 1 patients. The concomitant use of N 2 O reduces this requirement to as low as 2.5 μg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…[3] There is little information on the use of intravenous propofol for shoulder arthroscopy as the primary anaesthetic agent. Souron and colleagues,[4] reported the use of target control infusion (TCI) of propofol as a sedative during shoulder surgery under inter-scalene brachial plexus block. TCI propofol and single agent anaesthesia with sevoflurane have been compared by different authors,[5] for spine surgeries, but in patients who received no regional anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that intraoperative sedation is not a major triggering factor for HBEs [8,9]. Souron et al [51] demonstrated that in a single observation group, with 140 patients, target-controlled propofol infusion (0.8-0.9 µg/ml) following hydroxyzine premedication is a safe and effective technique for sedation when combined with ISBPB during shoulder surgery in the sitting position. The incidence of HBEs in their study was 5.7% (8 patients).…”
Section: New Contributing Factors For Hbesmentioning
confidence: 99%